A feasible strategy of fabricating hybrid drugs co-loaded polymer-lipid nanoparticles for the treatment of nasopharyngeal cancer therapy. (December 2021) - Yu, Fei; Zhang, Feng
Graphical abstract: Highlights: Hybrids nanoparticles with gefitinib (GEF) and apatinib (APT) was established (GEF-APT-LPHNs). GEF-APT-LPHNs morphology was investigated by TEM and DLS analysis. The in vitro proliferation assay displayed that the superior activity against the CNE2 and SUNE1 cells. The morphological features of the cells were established by staining methods. In vitro assay for the assessment of hemolytic properties of nanoparticles were established. Abstract: Effective novel therapies are required for nasopharyngeal cancers since nasopharyngeal patients are dysfunctional, and treatment remains a significant challenge. Here, a co-loading core-shell structured lipid-polymeric hybrids nanoparticles with gefitinib (GEF) and apatinib (APT) was established (GEF-APT-LPHNs). The LPHNs size, polydispersive index (PDI), zeta potential, and drug release properties were effectively investigated. The in vitro proliferation assay and cellular uptake displayed superior activity against the CNE2 and SUNE1 cells. Further, the morphological features of the CNE2 and SUNE1 cells were established by the dual staining method and nuclear damage staining strategy. Additionally, we evaluated an in vitro assay to assess the hemolytic properties of nanoparticles and discuss with the experiment the observed nanointerference. To prevent misleading effects from nanoparticles, we are proposing alternate approaches, debating the possible importance of nanoparticles in vitro systems.